(untitled) (Zia e Tahqeeq, 2025)
A mosque occupies central position in muslim society regarding development of ethics and morality. Mosques are source of identification for the Muslims. Mosques have been used as worship plece along with schooling, court and as a centre of cultural activities. The poets of Urdu language have also reflected on the topic of mosque. In this article the researcher has reviewed the poems of Jagan Nath Azad and Khawar Jelani where Jamia Masjid Dehli has mentioned specifically."Jamia Masjid ki Dehli" and "Dehli ki Jamia Masjid" are poems of Jagan Nath Azad and Khawar Jilani respectively. Both poets present two different narratives in terms of subject, style. The poem of Jagan Nath Azad is in the six lined stanza appearance and more in proximity in style with Allama Iqbla’s poem “Masjid-e-Qartaba”. According to Jagan Nath Azad, a world of thought is hidden in the each brick of Jamia Masjid of Dehli and this mosque is the custodian of all religious and social activities of Muslims. Reading Khawar Jilani’s poem “Dehli ki Jamia Masjid” one feels the pages of past turning. In the reign of Auranzaib Alamgir, Sarmad was captured and killed here in front of the mosque. The sole thought of the poem is related with Sarmad’s entity. A contrastive study has been conducted in this paper.